2001
DOI: 10.1111/j.1741-3737.2001.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Family Structure Matter? A Comparison of Adoptive, Two‐Parent Biological, Single‐Mother, Stepfather, and Stepmother Households

Abstract: ࡗ Does Family Structure Matter? A Comparison of Adoptive, Two-Parent Biological, Single-Mother, Stepfather, and Stepmother Households Using data from the National Survey of Families and Households, we compared quality of family relationships and well-being across five different family structures with a particular focus on adoptive households. Four theoretical perspectives, each emphasizing the importance of different factors in determining relationship quality and wellbeing, guided this work and led us to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
156
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(186 citation statements)
references
References 30 publications
17
156
2
6
Order By: Relevance
“…Rather, research suggests that family processes, such as parenting quality and attachment, are more important predictors of child outcomes than is family structure. These associations have been found both in biological and adoptive families, and among families with lesbian, gay parents and heterosexual parents (e.g., Chan et al, 1998;Erich, Kanenberg, Case, Allen, & Bogdanos, 2009;Lansford, Ceballo, Abbey, & Stewart, 2001). These family process variables are likely to emerge as more important than parental sexual orientation to child and parent outcomes in adoptive families with lesbian, gay, and heterosexual parents, but these issues have not yet been explicitly studied.…”
Section: Research On Lesbian-and Gay-parented Familiesmentioning
confidence: 99%
“…Rather, research suggests that family processes, such as parenting quality and attachment, are more important predictors of child outcomes than is family structure. These associations have been found both in biological and adoptive families, and among families with lesbian, gay parents and heterosexual parents (e.g., Chan et al, 1998;Erich, Kanenberg, Case, Allen, & Bogdanos, 2009;Lansford, Ceballo, Abbey, & Stewart, 2001). These family process variables are likely to emerge as more important than parental sexual orientation to child and parent outcomes in adoptive families with lesbian, gay, and heterosexual parents, but these issues have not yet been explicitly studied.…”
Section: Research On Lesbian-and Gay-parented Familiesmentioning
confidence: 99%
“…Further evidence for the greater importance of family process over family structure comes from studies that have directly examined the relative contribution of each Demuth & Brown, 2004;Dunn et al, 1998;Farr et al, 2010;Golombok, Mellish, et al, 2013;Hetherington, 1989;Lansford, Ceballo, Abbey, & Stewart, 2001). These studies have shown that it is not family structure per se that influences the socioemotional well-being of children in different family forms.…”
Section: General Conclusionmentioning
confidence: 99%
“…Conversely, adoptive mothers of non-institutionalized domestic adoptees have reported more disagreements with their adolescents than biological mothers or stepmothers (Lansford, Ceballo, Abbey, & Stewart, 2001). …”
Section: Mothersmentioning
confidence: 99%